2007
DOI: 10.1111/j.1540-8175.2007.00417.x
|View full text |Cite
|
Sign up to set email alerts
|

Preserved Windkessel Function in Patients Following Reduction Aortoplasty of the Ascending Aorta

Abstract: RAA without external wrapping shows good long-term results in patients with a dilated ascending aorta who underwent concomitant cardiac procedures. Echocardiography is very accurate in measuring the ascending aortic diameter, which makes it a cost-effective diagnostic tool. Moreover, ascending aortoplasty without external wrapping preserves the important elastic properties, namely the Windkessel function. Follow-up of the cardiac function and aortic diameter can be performed easily and precisely in the outpati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…In contrast to the mesh sleeve used in PEARS surgery, woven tubular Dacron grafts used in Bentall and valve sparing root replacement operations are essentially non-compliant and highly stiff without any distensibility or Windkessel effect. Tremblay et al showed that woven Dacron graft is the stiffest of all the graft materials used in aortic reconstruction with the stiffness~25 times of the normal human aorta [13] and Bail et al showed that patients with Dacron graft replacement of the aorta had a systolic change in diameter of only 0.7 mm [26].…”
Section: Aortic Root Distensibility After Pears Surgerymentioning
confidence: 98%
“…In contrast to the mesh sleeve used in PEARS surgery, woven tubular Dacron grafts used in Bentall and valve sparing root replacement operations are essentially non-compliant and highly stiff without any distensibility or Windkessel effect. Tremblay et al showed that woven Dacron graft is the stiffest of all the graft materials used in aortic reconstruction with the stiffness~25 times of the normal human aorta [13] and Bail et al showed that patients with Dacron graft replacement of the aorta had a systolic change in diameter of only 0.7 mm [26].…”
Section: Aortic Root Distensibility After Pears Surgerymentioning
confidence: 98%
“…This has several advantages in the short and medium terms. These include avoiding the introduction of prosthetic material, shorter operative and bypass times and, as has been shown in other studies, preservation of Windkessel function [11]. Our analysis also adds long-term (mean nine years) satisfactory aortic diameters to this list.…”
Section: Discussionmentioning
confidence: 64%
“…We believe CT is a reliable and reproducible method of measuring the mid ascending aortic diameter. A recent German study, has shown trans-thoracic echocardiographic diameters correlate well with CT diameters of the mid ascending aorta [11], however ascending aortic diameters are rarely reported on routine post-operative trans-thoracic echo.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Loss of Windkessel function (increased aortic stiffness) increases systolic blood pressure, leading to increased LV afterload and LV hypertrophy. 9) Further in-vitro or animal studies, as well as an observational, clinical study, will be needed to clarify the Windkessel function and LV function, in order to determine the optimal indication for surgery in patients with ascending aortic aneurysm.…”
Section: Discussionmentioning
confidence: 99%